Oncolytic Virus Therapy for Glioblastoma Multiforme Concepts and Candidates - Wollmann, Guido; Ozduman, Koray; van den Pol, Anthony N. (LIPPINCOTT WILLIAMS \& WILKINS, 2012)
Twenty years of oncolytic virus development have created a field that is driven by the potential promise of lasting impact on our cancer treatment repertoire. With the field constantly expanding-more than 20 viruses have been recognized as potential oncolytic viruses-new virus candidates continue to emerge even as established viruses reach clinical trials. They all share the defining commonalities of selective replication in tumors, subsequent tumor cell lysis, and dispersion within the tumor. Members from diverse virus classes with distinctly different biologies and host species have been identified. Of these viruses, 15 have been tested on human glioblastoma multiforme. So far, 20 clinical trials have been conducted or initiated using attenuated strains of 7 different oncolytic viruses against glioblastoma multiforme. In this review, we present an overview of viruses that have been developed or considered for glioblastoma multiforme treatment. We outline the principles of tumor targeting and selective viral replication, which include mechanisms of tumor-selective binding, and molecular elements usurping cellular biosynthetic machinery in transformed cells. Results from clinical trials have clearly established the proof of concept and have confirmed the general safety of oncolytic virus application in the brain. The moderate clinical efficacy has not yet matched the promising preclinical lab results

next-generation oncolytic viruses that are either ``armed{''} with therapeutic genes or embedded in a multimodality treatment regimen should enhance the clinical results.
Keywords: Oncolytic virus; virotherapy; glioblastoma; glioma; clinical trial; herpes simplex; adenovirus; poliovirus; measles; Newcastle disease virus; reovirus; vesicular stomatitis virus; parvovirus; vaccinia virus; myxoma virus